Co‐production for service improvement: Developing a training programme for mental health professionals to enhance medication adherence in Black, Asian and Minority Ethnic Service Users - Iris Gault; Julia Pelle; Mary Chambers (Health Expectations, 2019)
Abstract Aim To co‐produce consensus on the key issues important in educating mental health‐care professionals to optimize mental health medication adherence in Black, Asian and Minority Ethnic (BAME) groups. Objectives To identify perceptions of factors enabling or disabling medication adherence. To achieve consensus on content and delivery of an educational intervention for mental health‐care professionals. Methods Data were collected from 2016 to 2018. Using individual interviews and a consensus workshop with carers and service users (SUs treated under the 1983 Mental Health Act 1983/revised 2007 for England and Wales), the experience of taking prescribed mental health medication and perspectives on adherence were explored. Data were analysed using 2‐stage qualitative coding via the software tool NVivo version 11 to analyse transcribed data and to produce the main explanatory categories. Results SU and carer participants' perspectives substantially altered the original research design. The need to educate students rather than trained professionals was emphasized, and they suggested that educational content should be packaged in a contemporary manner (a virtual reality experience). Findings indicated that education should focus upon understanding the impact of taking prescribed antipsychotic medication on both SUs and carers. Discussion The importance of effective communication between health professionals, SUs and carers and a willingness to learn about and appreciate how BAME culture influences perception of mental illness and mental well‐being were highlighted. Conclusion In working co‐productively, researchers need to be flexible and adaptable to change.